Leveraging corporate responsibility : the stakeholder route to maximizing business and social value - Bhattacharya, C B. (Cambridge University Press, 2011)
"The corporate social and environmental responsibility movement, known more generally as corporate responsibility (CR), shows little sign of waning. Almost all large corporations now run some form of corporate responsibility program. Despite this widespread belief that CR can simultaneously improve societal welfare and corporate performance, most companies are largely in the dark when it comes to understanding how their stakeholders think and feel about these programs. This book argues that all companies must understand how and why stakeholders react to such information about companies and their actions. It examines the two most important stakeholder groups to companies - consumers and employees - to comprehend why, when and how they react to CR. Armed with this insight, it shows how companies can maximize the value of their CR initiatives by fostering strong stakeholder relationships to develop, implement and evaluate compelling social responsibility programs that generate value for both the company and its stakeholders"--